Does living near heavy industry cause lung cancer in women? A case-control study using life grid interviews. Issue 12 (13th October 2006) - Edwards, R; Pless-Mulloli, T; Howel, D; Chadwick, T; Bhopal, R; Harrison, R; Gribbin, H
Abstract : Background: The incidence of lung cancer among women is high in the highly industrialised area of Teesside in north-east England. Previous research has implicated industrial pollution as a possible cause. A study was undertaken to investigate whether prolonged residence close to heavy industry is associated with lung cancer among women in Teesside. Methods: Two hundred and four women aged <80 years with incident primary lung cancer and 339 age matched community controls were recruited to a population based case-control study. Life course residential, occupational, and active and passive smoking histories were obtained using an interviewer administered questionnaire. Results: The age adjusted odds ratio (OR) for lung cancer among people living >25 years v 0 years near (within 0–5 km) heavy industry in Teesside was 2.13 (95% CI 1.34 to 3.38). After adjustment for confounding factors the OR was 1.83 (95% CI 0.82 to 4.08) for >25 years or 1.10 (95% CI 0.96 to 1.26) for an additional 10 years living near industry. ORs were similar after residence near heavy industry outside Teesside was also included, and when latency was allowed for by disregarding residential exposures within the last 20 years. Adjustment for active smoking had the greatest effect on the OR. Conclusions: This population based study using life grid interviews for life course exposure assessment has addressed many deficiencies in the design of previous studies. The findings support those in most of the international literature of a modestly raised risk of lung cancer with prolonged residence close to heavy industry, although the confidence intervals were wide. The effect of air pollution on the incidence of lung cancer merits continued study.